“All the proportions are changed”: twelfth night and the evolution of the concept and practice of mise en scène in Portugal - Paulo Eduardo Carvalho (Ilha do Desterro)
The actual persons of Malvolio, Sir Toby, Olivia and the rest expand our visionary characters out of all recognition. At first we are inclined to resent it. You are not Malvolio; or Sir Toby either, we want to tell them; but merely impostors. We sit gapping at the ruins of the play, at the travesty of the play. And then by degrees this same body or rather all these odies together, take our play and remodel it between then. The play gains immensely in robustness, in solidity. The printed word is changed out of all recognition when it is heard by other people. We watch it strike upon this man or woman; we see them laugh or shrug their shoulders, or turn aside to hide their faces. The word is given a body as well as a soul. Then again as the actors pause, or topple over a barrel, or stretch their hands out, the flatness of the print is broken up as by crevasses or precipices; all the proportions are changed. Virginia Woolf (208)